Development of a new cellular immunological detection method for tuberculosis based on HupB protein induced IL-6 release test - Yu, Xiaoli; Jiang, Shengsheng; Li, Yang; Zhou, Huaiheng; Wei, Yutong; Li, Xuefang; Zhang, Ye; Hu, Peng; Wu, Haoming; Wang, Hualin; Wu, Shimin; Zhang, Shulin (Frontiers in Microbiology, 2023)
Abstract Objective: As a virulence factor, HupB plays important roles in the survival of MTB after infection and modulates the host immune response. In the current study, we aim to explore a new cellular immunological detection method for tuberculosis infection detection based on HupB protein. Methods: HupB was used to stimulate PBMCs extracted from pulmonary tuberculosis (PTB) patients, and secreted cytokines was examined. Then, we constructed a single center and a multi-center clinical trials to collect PBMCs from PTB patients, nPTB patients, or healthy volunteers to verify our findings. Results: Cytokine’s screening illustrated that IL-6 was the only cytokine released after HupB stimulation. Single-center and multi-center clinical trials showed that HupB stimulation significantly increased the level of IL-6 in the supernatant of PBMCs from PTB patients. Then we compared the specificity and sensitivity of HupB induced IL-6 release assay with ESAT-6 and CFP10 induced interferon γ release assay (IGRA), and found in smear positive PTB patients, the specificity and sensitivity of HupB induced IL-6 release assay was better than IGRA, and in smear negative PTB patients, the sensitivity was better. Combination of both assays provided an improved specificity and sensitivity for tuberculosis diagnosis. Conclusion: This study explored an immunological detection method for tuberculosis infection cells based on HupB protein-induced IL-6 release test, which can be used to enhance the diagnosis diagnostic accuracy of TB.